Seminal Corynebacterium strains in infertile men with and without leucocytospermia. (31st July 2015) - Mashaly, M.; Masallat, D. T.; Elkholy, A. A.; Abdel‐Hamid, I. A.; Mostafa, T.
Summary: This study aimed to identify seminal Corynebacterium strains in infertile men with and without leucocytospermia. Semen samples from 60 infertile men were allocated into two equal groups: semen samples with leucocytospermia and semen samples without leucocytospermia. Semen culture for Corynebacterium species was carried out on Columbia agar medium confirmed by Gram‐stained film and biochemical tests followed by analytical profile index biotyping and antibiotic susceptibility. Bacterial isolates were detected in 20/60 semen cultures (33.3%) as Corynebacteria, Staphylococci, Alpha haemolytic streptococci and E. coli . In all, 12/60 (20%) had Corynebacterium positive semen culture, whereas C. seminal was the major isolated species followed by C. amycolatum, C. jekium and C. urealyticum . There was nonsignificant difference between patients with/without Corynebacterium positive culture regarding sperm concentration and normal sperm morphology; however, in positive cultures sperm motility was significantly lower compared with negative cultures. Antimicrobial sensitivity among Corynebacteria strains was highest for vancomycin, rifampicin then imipenem, ampicillin + sulbactam, ciprofloxacin. It is concluded that positive semen cultures for different Corynebacteria species were demonstrated in infertile men, whereas Corynebacterium seminale was the most common isolated species. Vancomycin, rifampicin then imipenem and ampicillin + sulbactam are recommended as sensitive antibiotics.